Outstanding Reviewer Award in the 2024 Emerald Literati Awards - Zarkada, Anna K. (My University, 2026)
! We are happy to announce that you have been awarded an Outstanding Reviewer Award in the 2024 Emerald Literati Awards, selected by the editorial team of International Journal of Bank Marketing. Your hard work and dedication have truly paid off, and this remarkable accomplishment deserves to be celebrated far and wide! We encourage you to share this exciting news with your network and colleagues, as it truly deserves to be seen and acknowledged.
Keywords: Social sciences